ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH AKUISISI (STUDY PADA PERUSAHAAN PENGAKUISISI YANG TERDAFTAR DI BEI PERIODE 2000-2011) - IRA APRILITA; RINA TJANDRAKIRANA DP; ASPAHANI . (Program Studi Magister Manajemen FE Unsri, 2013)
This research is to analyze the company's financial performance comparison before and after the acquisition. Is there a significant difference or not, and the difference is increased or decreased. Financial performance here is measured by the ratio of ROI, ROE, DER, TATO, CR, and EPS. This study takes population from all company that acquisition activity in period 2000-2011. The samples in this study using purposive sampling method, andÂ and obtained a sample of 17 companies in the period 2000-2011, with the appropriate criteria have been determined, the ratio of data obtained from the Indonesian Capital Market Directory (ICMD). The analysis used to test the hypothesis of this research is quantitative analysis with Wilcoxon Signed Rank Test and Manova. Based on descriptive statistics, changes in the average value (mean) of the ratio of DER, tato and EPS have increased, but the results are not strong enough to prove the existence of significant differences in financial performance as measured by these ratios. The Test results using the Wilcoxon Signed Rank Test showed that there was no significant difference for all ratios after the acquisition, and it is also supported by the results of testing with Manova.